O que acontece embaixo da ponte? : juventudes e ocupação de espaço público - Pereira, Renata de Mello Cerqueira (2016)
The growth of the city of Aracaju, Northeast Brazil, brings questions about the occupation of urban spaces. In the case of this research, the starting point to study the cultural space created after the construction of the bridge linking the capital Aracaju the county of Barra Dos Coqueiros came from the Industrial District. Using an Ethnography done through field research, participant observation, interviews and questionnaires, relevant information was gathered about the “Sintonia Periférica” group, which occupies the space under the bridge in an artistic and political manifestation through the hip-hop movement. This research aimed to observe and analyze the way the young people of this town have been occupying and transforming the space, and the relationships that this artistic intervention in public spaces have with the reurbanization and growth of the city. To perceive the dimension of the relationships and their modes of action, consequent of urban restructuring, demonstrate the various possible ways of new forms of social and structural organization of the city, with relevance to the knowledge not only to social sciences, but also for the Public Administration and the community in general, because actions like these are daily response to the way the city has been ordered and its consequences in everyday life of its residents.